EFEK PENGGUNAAN PRODUK GELATINISASI EMPULUR GEWANG DENGAN UREA TERHADAP PERTUMBUHAN SAPI BALI YANG MENGKONSUMSI RUMPUT ALAM (The effect of use gelatinized gewang pith with urea product on bali cattle growth which consumption of natural grass) - Edwin jermias lazarus; Emma Dyelim Wie Lawa (JURNAL NUKLEUS PETERNAKAN, 2020)
The purpose of this study was to determine the effect of using the pith gewang gelatinized with urea on the growth of the bali cattle that received natural grass as basal ration. Fifteen male bali cattle were allocated to get one of the three ration treatments, namely, gewang pith mixed with urea (R0), product gelatinized gewang pith with urea as much 15% (R1) and the product of gelatinized gewang pith with urea as much 30% (R2). A completely randomized design was used as a trial design with 3 treatments and 5 replications. Research data were analysis of variance and Duncan’s multiple range test. The results of the study showed that use product of gelatinized gewang pith with urea increased consumption, digestibility, weight gain and feed efficiency of bali cattle ration (P<0,01). The response of bali cattle was higher in the use of product gelatinized gewang pith with urea in the ration compared to mixture of gewang pith with urea. The use of gelatinized product as much 30% in the ration was significantly higher than the use of as much 15%. It was concluded that the use of gelatinized product of pith gewang with urea as supplement in the ration increased consumption, digestibility, weight gain and feed efficiency of bali cattle which consumption natural grass compared to the use of mixed gewang pith with urea. The highest growth response was shown by bali cattle that received product of gelatinized gewang pith with urea as much 30% in the ration.